Prevalence of the bullying phenomenon in a schools sample of Palermo, Sicily: a pre-post intervention observational study among teachers: Bullying prevalence in sicilian schools - Costantino, Claudio; Ventura, Gianmarco; Marotta, Claudia; Bono, Stefania Enza; Arcidiacono, Evelina; Gambino, Carlo Roberto; Gentile, Maurizio; Palmeri, Sara; Ripoli, Giovanna; Sannasardo, Claudia Emilia; Sannasardo, Pierfrancesco; Scarpitta, Francesco; et al. (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Bullying involves a significant percentage of school-age children. According to the latest available surveillance data, in Sicily, the estimated prevalence among 11-15 years old children is 14%. This study aimed to estimate a prevalence of the bullying phenomenon, observed by teachers, in a sample of secondary schools of Palermo, Sicily. Moreover, after the conduction of preventive interventions among teachers, aimed to evaluate any modification in bullying prevalence. Methods: A cluster sampling selection according to socio-economic level of the school neighborhood was carried out. Two anonymous online questionnaires, pre and post-intervention, were administered to the 63 teaching staff, belonging to second and third year classes of ten secondary schools enrolled. Preventive interventions were conducted among teachers by experienced researchers. Results: Prevalence of bullying reported decreased significantly from 44.4% to 19.0% (p-value 0.001), comparing pre and post-intervention questionnaires. A reduction in the prevalence of verbal and physical bullying and a concomitant slight increase of indirect bullying were also observed. All the characteristics, reported by the teaching staff, for describing bullies, victims and observers of bullying have been categorized under three different content domains (affective-relational discomfort, socio-cultural context, and character/natural disposition). Conclusions: The present study estimated the prevalence and the characteristics of bullying phenomenon in a sample of secondary schools of Palermo, evaluating the reduction of bullying episodes among students, after a preventive interventions conducted among teaching staff. Data obtained confirmed the effectiveness of this approach and suggested an extension of the project at Regional Level.